2010
DOI: 10.1002/ffj.2008
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of volatile components of Teucrium massiliense L. – identification of 6‐methyl‐3‐heptyl acetate as a new natural product

Abstract: Volatile components extracted from the aerial parts and separated organs of Corsican and Sardinian Teucrium massiliense have been studied. The chemical composition of essential oils obtained by hydrodistillation (HD) has been investigated using GC-RI, GC-MS (EI and CI modes) and 13 CNMR spectroscopy. For the first time, a real concentration via calibration curves and response factor calculations has been determined for each oil component. The concentrations of the major components were 6-methyl-3-heptyl acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…With these RFs, the components of the essential oil can be quantified through the following equation: CVOC=Aabs,VOC/Aabs,IS×CIS×RF/Woil×100where C VOC is the concentration expressed as g/100 g of essential oil of the target volatile compound, A abs,VOC is its absolute peak area, W oil is the weight of the oil expressed in grams, and the other terms are as stated above. This approach was successfully applied to the quantification of Calendula arvensis and Teucrium massiliense essential oil components. For the study of seasonal variations, the concentrations of each compound were expressed in mg/100 g of dried plant through the following equation: CVOCmg/100g dried plant=CVOCg/100gEO×yield(w/dw)/100where C VOCmg/100g dried plant is the concentration of the target volatile expressed in mg/100 g of dried plant, C VOCg/100gEO is the concentration of the target volatile expressed in g/100 g of essential oil, yield (w/dw) is the yield oil expressed in % from the weight of dried plant material.…”
Section: Methodssupporting
confidence: 65%
“…With these RFs, the components of the essential oil can be quantified through the following equation: CVOC=Aabs,VOC/Aabs,IS×CIS×RF/Woil×100where C VOC is the concentration expressed as g/100 g of essential oil of the target volatile compound, A abs,VOC is its absolute peak area, W oil is the weight of the oil expressed in grams, and the other terms are as stated above. This approach was successfully applied to the quantification of Calendula arvensis and Teucrium massiliense essential oil components. For the study of seasonal variations, the concentrations of each compound were expressed in mg/100 g of dried plant through the following equation: CVOCmg/100g dried plant=CVOCg/100gEO×yield(w/dw)/100where C VOCmg/100g dried plant is the concentration of the target volatile expressed in mg/100 g of dried plant, C VOCg/100gEO is the concentration of the target volatile expressed in g/100 g of essential oil, yield (w/dw) is the yield oil expressed in % from the weight of dried plant material.…”
Section: Methodssupporting
confidence: 65%
“…Regarding Teucrium massiliense , our results confirmed a very high variability. The main compounds detected in the EO, according to previous reports [ 5 , 49 ] were 6-methyl-3-heptyl acetate (23.55%), followed by γ-muurolene (10.97%), (E)-β-farnesene (8.44%), ar-curcumene (7.56%), 3-octenyl acetate (7.33%), α-zingibergene (6.37%), and (Z)-α-bisabolene (5.85%). Djabou et al [ 49 ] reported the 6-methyl-3-heptyl acetate for the first time as a natural compound in Corsican and Sardinian oil obtained from T. massiliense .…”
Section: Resultsmentioning
confidence: 99%
“…The procedure included the calcul of FID response factors (RFs) relative to an internal standard. We carried out a methodology reported in the literature [36] and improved in our laboratory [37]. The application of this analytical procedure allowed the determination of the oil component relative concentrations expressed in g/100 g of essential oil.…”
Section: Methodsmentioning
confidence: 99%